Knowledge, Attitude, and Practice Regarding COVID-19 Among Healthcare Workers in Primary Healthcare Centers in Dubai: A Cross-Sectional Survey, 2020 - Albahri, Abdulaziz Hussain; Alnaqbi, Shatha Ahmed; Alnaqbi, Shahad Ahmed; Alshaali, Asma Obaid; Shahdoor, Shaikha Mohammad (Frontiers in Public Health, 2021)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic continues to challenge healthcare services worldwide. Healthcare workers (HCWs) are key to the continued effort to overcome the pandemic. This study aims to evaluate the knowledge, attitude, and practices of HCWs toward COVID-19 in primary health centers in Dubai. Methods: This cross-sectional study was conducted at four primary health centers in Dubai, including two fever clinics, from July 5th to July 11th, 2020. A self-administered online questionnaire was distributed to nurses and physicians working in these centers, which evaluated their knowledge, attitude, and practices regarding COVID-19 and their associations with the participants' demographic factors. A total score of 80% and above constituted a level of sufficiency in each section. Additionally, Mann-Whitney U test and multivariable logistic regression were used to analyze the variables. Results: A total of 176 HCWs completed the questionnaire, with a 91.2% (176/193) response rate. They were predominantly female (158/176, 90.0%), nurses (128/176, 72.7%), and non-Emiratis (150/176, 85.2%). While official health organizations were the primary source of information for 91.5% (161/176) of participants, only 38.1% (67/176) reported using scientific journals as one of their sources. Overall, 57.4% (101/176) of participants had a sufficient overall level of knowledge. Moreover, knowledge regarding signs, symptoms, and at-risk groups was generally satisfactory. However, knowledge about the virus, testing, transmission, and the isolation of contacts with positive cases was identified correctly by less than two-thirds of the participants. Half of the participants (89/176, 50.6%) expressed their concern about personally acquiring the infection, 112/176 (63.6%) worried about their relatives acquiring it, and 72/176 (40.9%) expressed some hesitancy to take the COVID-19 vaccine once available. Overall, only 58/176 (33.0%) HCWs had a sufficient overall positive attitude score. Nurses, compared to physicians, and non-Emiratis compared to Emiratis' HCWs, had statistically higher mean scores for attitude (U = 2,212, p < 0.01; and U = 1164.5, p < 0.01, respectively). The majority of participants (156/176, 88.6%) reported acceptable infection control practices. Conclusion: Given the gaps identified in the knowledge and attitude, we recommend further training to improve the skills of primary HCWs, with encouragement to practice evidence-based medicine. Additionally, further exploration regarding vaccine hesitancy is warranted.